Second Five Year Plan Volume I Saharanpur District Uttar Pradesh - Planning Commission (Planning Commission, 1955)
During this period the country has made garrulous achievements which are known to ovary body. Particular attention drawn achieved on the Food Front and in the field of Irrigation and Community Projects and National Extension Service Blocks. Having been encouraged by the astounding of the First Five Year Plan, Second Five Year Plan is now being drawn where it is contemplated to cover the entire rural population of the district by the Community Project and Rational Extension Service Blanks by 1996-99.
Planning Department, Uttar Pradesh